CHARACTERISTIC OF FRESH SEMEN OF BALI BULL AT BATURITI ARTIFICIAL INSEMINATION CENTER - I.P.G.D, Widiarta; Sumardani, N.L.G.; Mariani, N.P. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the parameters of fresh semen quality of bali bull at Baturiti Artificial Insemination Center. Primary data is obtained from surveys techniques, interviews, and on the job training, while secondary data is obtained through records of fresh semen storage results for the bali bull during October 2018 at Baturiti Artificial Insemination Center. The variables observed in this study included: volume, color, percentage of individual motility, concentration of spermatozoa, and amount of frozen semen production. The results showed that the average characteristics of fresh semen of bali bull at Baturiti Artificial Insemination Center in October 2018 consisted of semen volume were 6,7 ml, semen of bali’s bull dominated by the cream color, individual motility percentage were 69%, spermatozoa concentration were 1.175 million/ml and the production of frozen semen is 15.343 straw. The conclusions showed in general the characteristics of fresh semen of bali bull at Baturiti Artificial Insemination Center include volume, color, percentage of individual motility, spermatozoa concentration in accordance with standards and the amount of frozen semen production according to target and frozen semen is suitable for distribution. Keywords: characteristic semen, spermatozoa, fresh semen, bali bull